2011
DOI: 10.1007/jhep03(2011)141
|View full text |Cite
|
Sign up to set email alerts
|

Wilsonian approach to fluid/gravity duality

Abstract: The problem of gravitational fluctuations confined inside a finite cutoff at radius r = r c outside the horizon in a general class of black hole geometries is considered. Consistent boundary conditions at both the cutoff surface and the horizon are found and the re- The ratio is expected to run when quantum gravitational corrections are included.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
287
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(312 citation statements)
references
References 71 publications
23
287
2
Order By: Relevance
“…[28]. Here the effective gravitational dynamics of the D3-brane subject to Dirichlet boundary conditions at an appropriate cutoff surface was considered along the lines of ideas introduced in the paper(s) [29,30]. It was directly shown that the fluid/gravity correspondence and the hydrodynamic effective theory are obtained as the two (most interesting) extremes where the cutoff surface is taken to be located in the near-horizon throat region and at spatial infinity, respectively.…”
Section: Jhep04(2015)171mentioning
confidence: 99%
“…[28]. Here the effective gravitational dynamics of the D3-brane subject to Dirichlet boundary conditions at an appropriate cutoff surface was considered along the lines of ideas introduced in the paper(s) [29,30]. It was directly shown that the fluid/gravity correspondence and the hydrodynamic effective theory are obtained as the two (most interesting) extremes where the cutoff surface is taken to be located in the near-horizon throat region and at spatial infinity, respectively.…”
Section: Jhep04(2015)171mentioning
confidence: 99%
“…In particular, recent progress on the Wilsonian approach to Fluid/Gravity duality has opened a new window to link the Einstein equation to the Navier-Stokes equation for a general class of spacetime geometries [11][12][13]. In this setup the gravitational fluctuations are confined inside the region between the horizon and a finite cutoff at radius r = r c , and a dual holographic fluid lives on the cutoff surface.…”
Section: Introductionmentioning
confidence: 99%
“…We can now insert this into the PE (19) and integrate by parts. We assume that this can be done smoothly.…”
Section: The Wilsonian Rgmentioning
confidence: 99%
“…It was also suggested [10][11][12][13][14] that the holographic RG could be explicitly related to Polchinski's "exact" formulation of the Wilsonian RG [15]. Very recently, these ideas echoed through a series of works commenting on relations between different aspects of holographic and Wilsonian RGs [16][17][18][19]. Nevertheless, we still lack a precise statement on how to reach the bulk dual of a QFT by computing its Wilsonian RG flow.…”
Section: Introductionmentioning
confidence: 99%